NILAI ANAK PADA KELUARGA SUKU TALANG MAMAK DI DESA TALANG DURIAN CACAR KECAMATAN RAKIT KULIM KABUPATEN INDRAGIRI HULU - Merri Mariyani; Syamsul Bahri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Mamak tribe community to a change is something that can not be denied. Currently Talang Mamak community little by little leads to modern life, ranging from clothing, the form of houses, education to information and communication technology they have started to use. So the child becomes the place of the parents to rely on the hope of a better life in the future. Parents' perceptions of the value of the child affect the number of children desired. When parents feel the child has great benefits or usefulness then the parents will choose to have many children. But if the parents feel the cost or the burden of raising a child is high, then the parents will want fewer children. Each parent has a different view of the child's desired sex. This research was conducted with the aim to know the view of the value of children according to gender in Talang Mamak tribe culture and which gender is considered high according to the community kinship system Talang Mamak tribe. Methods in this study using qualitative data analysis, data collected and then presented descriptively, with the technique of sampling non probability and the technique used is purposive sampling. The subject of this research is the customary figures and members of Talang Mamak tribe community in the village of Talang Durian Cacar. This study uses data obtained through observation, interviews and documentation. The results showed that Talang Mamak community preferred to have many children between 4-6 people. They prefer to have more daughters than boys. Children in addition to having a positive value also has a negative value that is a burden for parents. But the Talang Mamak community does not consider the child as a burden but it is the parent's responsibility to the child.Keywords: Value of children, Talang Mamak Tribe.